REACTION BETWEEN Shigella dysentriae SUBUNIT PILI ANTIGEN WITH 18 KDA Shigella flexneri SUBUNIT PILI ANTIBODY - Avin Ainur Fitrianingsih, M. Biomed. (El-Hayah, 2022)
Shigellosis caused by S. flexneri and S. dysentriae is the leading cause of death in developing countries. Meanwhile, the development of the Shigella vaccine is still ongoing. This study aims to prove the reaction between the 18 kDa S. flexneri pili sub-unit protein's antibodies and with the S. dysentriae pili sub-unit protein antigen. This study used the Western Blot and Dot Blot tests to determine the antibody-antigen reaction both qualitatively and quantitatively.  From the study results, it was found that the 18 kDa S. flexneri 18 kDa pili subunit protein was able to recognize the S. dysentriae pili sub-unit protein with a molecular weight of 17 kDa and 23 kDa. The protein subunit pili S. dysentriae with a molecular weight of 17 kDa and 23 kDa probably has an epitope recognized by the antibody to the pili protein subunit S. flexneri 18 kDa. The equivalent zone of the antibody-antigen reaction lies in the concentration of the antibody protein subunit pili 18 kDa S. flexneri titer 1/300 and the concentration of the antigen protein subunit pili 18 kDa S. dysentriae titer 1/20. So that the higher the dilution of the antibody of the 18 kDa S. flexneri pili subunit, the lower the bond with the S. dysentriae pili subunit antigen.